Can the success of structured therapy for giggle incontinence be predicted? - Onur Telli; Nurullah Hamidi; Aytac Kayis; Evren Suer; Tarkan Soygur; Berk Burgu (International Brazilian Journal of Urology, 2016)
ABSTRACT Introduction: To evaluate possible factors that can guide the clinician to predict potential cases refractoriness to medical treatment for giggle incontinence (GI) and to examine the effectiveness of different treatment modalities. Material and methods: The data of 48 children referred to pediatric urology outpatient clinic between 2000 and 2013 diagnosed as GI were reviewed. Mean age, follow-up, GI frequency, associated symptoms, medical and family history were noted. Incontinence frequency differed between several per day to less than once weekly. Children were evaluated with uroflowmetry-electromyography and post-void residual urine. Clinical success was characterized as a full or partial response, or nonresponse as defined by the International Children's Continence Society. Univariate analysis was used to find potential factors including age, sex, familial history, GI frequency, treatment modality and dysfunctional voiding to predict children who would possibly not respond to treatment. Results: Mean age of the patients was 8.4 years (range 5 to 16). Mean follow-up time and mean duration of asymptomatic period were noted as 6.7±1.4 years and 14.2±2.3 months respectively. While 12 patients were treated with only behavioral urotherapy (Group-1), 11 patients were treated with alpha-adrenergic blockers and behavioral urotherapy (Group-2) and 18 patients with methylphenidate and behavioral urotherapy (Group-3). Giggle incontinence was refractory to eight children in-group 1; six children in-group 2 and eight children in-group 3. Daily GI frequency and dysfunctional voiding diagnosed on uroflowmetry-EMG were found as outstanding predictive factors for resistance to treatment modalities. Conclusions: A variety of therapies for GI have more than 50% failure rate and a standard treatment for GI has not been established. The use of medications to treat these patients would not be recommended, as they appear to add no benefit to symptoms and may introduce severe adverse effects.